Soybean Planting Date × Maturity Group: Eastern Kansas Summary - I. A. Ciampitti; D. E. Shoup; G. Sassenrath; J. Kimball; E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2015)
Optimum planting time for soybean depends on the interaction between genotype and environment (G × E). Four field studies were conducted during the 2014 growing season across eastern Kansas (Manhattan, Topeka, Ottawa, and Parsons). This study explores the impact of planting date (early, mid, and late planting times) on yield for modern soybean cultivars from a range of maturity groups (early, medium, and late groups).
Keywords: soybean; planting date; maturity group; yield